Differentiation of Bolboschoenus maritimus (L.) Palla in Polish maritime populations on the basis of inflorescences and pollen grains parameters - Kreft, Anna (Biodiversity: Research and Conservation, 2006)
The aim of this work is to define the intraspecific differentiation of maritime populations of Bolboschoenus maritimus (L.) Palla in Poland on the basis of the inflorescences and pollen grains parameters. In the investigated maritime populations of B. maritimus, both the representative of B. maritimus var. maritimus and B. maritimus var. compactus were occurred, yet B. maritimus var. compactus was less frequent component of the vegetation. The dependence between the size of pollen grains and the distinguished varieties of this taxon has not been noticed. The number and the length of the peduncles of the inflorescence, the ratio of the number of sessile spikelets to pedunculate spikelets, the number of pedunculate spikelets, the ratio of length of sessile spikelets to the length of pedunculate spikelets are the parameters which most clearly distinguish B. maritimus var. maritimus from B. maritimus var. compactus. A higher differentiation of analysed parameters of inflorescences was observed for B. maritimus var. compactus.